2020
DOI: 10.1029/2020gl089063
|View full text |Cite
|
Sign up to set email alerts
|

Record‐Low Arctic Stratospheric Ozone in 2020: MLS Observations of Chemical Processes and Comparisons With Previous Extreme Winters

Abstract: Aura Microwave Limb Sounder (MLS) measurements show that chemical processing was critical to the observed record‐low Arctic stratospheric ozone in spring 2020. The 16‐year MLS record indicates more polar denitrification and dehydration in 2019/2020 than in any Arctic winter except 2015/2016. Chlorine activation and ozone depletion began earlier than in any previously observed winter, with evidence of chemical ozone loss starting in November. Active chlorine then persisted as late into spring as it did in 2011.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
160
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 126 publications
(186 citation statements)
references
References 32 publications
(71 reference statements)
26
160
0
Order By: Relevance
“…Stratospheric ozone values over large parts of the Arctic reached record low values in March and April 2020 (Manney et al, 2020) with ozone severely depleted between mid-March and mid-April 2020 when ozonesondes observed minimum mixing ratios of 0.1-0.2 ppm around 17-19 km (Wohltmann et al, 2020), lower than observed in any previous year. Model simulations and evaluation against MLS data by Groß and Müller (2020) also confirmed these findings.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Stratospheric ozone values over large parts of the Arctic reached record low values in March and April 2020 (Manney et al, 2020) with ozone severely depleted between mid-March and mid-April 2020 when ozonesondes observed minimum mixing ratios of 0.1-0.2 ppm around 17-19 km (Wohltmann et al, 2020), lower than observed in any previous year. Model simulations and evaluation against MLS data by Groß and Müller (2020) also confirmed these findings.…”
Section: Introductionmentioning
confidence: 75%
“…Lawrence et al (2020) showed that the record breaking strong polar vortex in winter/spring 2020 developed as a combination of weak wave driving from the troposphere and a wave-reflecting configuration in the upper stratosphere. The 2020 Arctic polar vortex was cold enough to allow PSCs to form (Manney et al, 2020), leading to large stratospheric ozone losses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the combination of the persistent polar processing conditions conducive for chemical loss and the persistently low column ozone values point to chemical depletion in 2019/2020 being a large factor. Further, Manney et al (2020) show evidence of chemical loss in vertically resolved ozone profiles matching or exceeding that in 2011.…”
Section: Polar Processing and Ozone Lossmentioning
confidence: 85%
“…A connection between Arctic ozone variability and extratropical surface is probably mediated by the dynamical variability that typically drives the anomalous ozone concentrations rather than the opposite (Harari et al, 2019). Manney et al (2020) recently reported on the chemical processes during the extreme ozone loss in March 2020; however, the predictability of the extreme ozone loss in March 2020 (andin March 1997 and and of the subsequent surface impact has still not been explored. This paper focuses on the general -hPa height (units: km, right column) in late winter (February-March, FM hereafter) from 1979 to 2020 in the ERA5 reanalysis.…”
Section: Introductionmentioning
confidence: 99%